2012
DOI: 10.3390/biom2040549
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidases Have Strong Hydrolytic Activity toward Chondroitin 4-Sulfate Comparable to that for Hyaluronan

Abstract: Chondroitin sulfate (CS) chains are involved in the regulation of various biological processes. However, the mechanism underlying the catabolism of CS is not well understood. Hyaluronan (HA)-degrading enzymes, the hyaluronidases, are assumed to act at the initial stage of the degradation process, because HA is similar in structure to nonsulfated CS, chondroitin (Chn). Although human hyaluronidase-1 (HYAL1) and testicular hyaluronidase (SPAM1) can degrade not only HA but also CS, they are assumed to digest CS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…Testicular hyaluronidase has been known to show a preference towards HA over Ch4S as a hydrolysis substrate and that was consistent at pH 5, 37 • C (typical condition), whereas it showed a preference towards Ch4S over HA in selective conditions such as at pH 6, 45 • C (Knudson, Gundlach, Schmid, & Conrad, 1984). Recently, it was demonstrated that Ch4S is a better substrate than HA for testicular hyaluronidase (recombinant SPAM1) at pH 4 or lower pH, whereas HA is a better substrate than Ch4S above pH 4 (Honda, Kaneiwa, Mizumoto, Sugahara, & Yamada, 2012). In either condition in both reports Ch6S was a poorer substrate than HA and Ch4S.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Testicular hyaluronidase has been known to show a preference towards HA over Ch4S as a hydrolysis substrate and that was consistent at pH 5, 37 • C (typical condition), whereas it showed a preference towards Ch4S over HA in selective conditions such as at pH 6, 45 • C (Knudson, Gundlach, Schmid, & Conrad, 1984). Recently, it was demonstrated that Ch4S is a better substrate than HA for testicular hyaluronidase (recombinant SPAM1) at pH 4 or lower pH, whereas HA is a better substrate than Ch4S above pH 4 (Honda, Kaneiwa, Mizumoto, Sugahara, & Yamada, 2012). In either condition in both reports Ch6S was a poorer substrate than HA and Ch4S.…”
Section: Discussionmentioning
confidence: 87%
“…In either condition in both reports Ch6S was a poorer substrate than HA and Ch4S. Their kinetic data suggested that testicular hyaluronidase has higher affinity for Ch4S and HA than for Ch6S (Honda et al, 2012). These findings may explain why that when both the chain length and sufation degree are similar Ch4S oligosaccharides are better inhibitors than Ch6S oligosaccharides for BTH from the aspect of the affinity with the enzyme.…”
Section: Discussionmentioning
confidence: 94%
“…Hyaluronidase (HASE) and chondroitinase (CASE) are two enzymes that are active upon CS in vivo [20][21][22]. We used both enzymes in our studies aiming validation of the proposed method for different substrates and enzymes.…”
Section: Biochemical Information About the Digestionmentioning
confidence: 99%
“…The optimum pH for maximum hydrolytic activity of HAase is 4 to 5 (37,38). However, it has been reported that HAase exert its activity at weakly acidic (pH 5 to 6) (38) and alkaline conditions (pH 7 to 8) (37,39). The bovine testicular HAase was used as a model enzyme, since it is commercially available and, like human HAase, it catalyzes the hydrolysis of the β(1-4) glycosidic bonds in HA (40).…”
Section: Enzymatic Degradation Analysis Of Ha-npsmentioning
confidence: 99%